2005
DOI: 10.1016/j.biologicals.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

SARS-coronavirus (SARS-CoV) and the safety of a solvent/detergent (S/D) treated immunoglobulin preparation

Abstract: SARS-coronavirus (SARS-CoV) is a newly emerged, highly pathogenic agent that caused over 8000 human infections with nearly 800 deaths between November 2002 and September 2003. While direct person-to-person transmission via respiratory droplets accounted for most cases, other modes have not been ruled out. SARS-CoV viraemia does not seem to reach high titres, however, it has to be excluded that virus transmission may occur via blood transfusion or application of therapeutic plasma products, e.g. fresh-frozen pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 18 publications
(25 reference statements)
4
42
0
Order By: Relevance
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…In addition, SARS-CoV was found to be sensitive to solvent and detergent, such as TNBP/Triton X-100, TNBP/Tween 80, and sodium cholate [49]. After 30-minute treatment using S/D produced by Octaplas (Octapharma), the virus was reduced more than 5.75 ± 0.3 log 10 TCID 50 /mL [50].…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…In 1985 and before, Horowitz and his group reported that the solvent/ detergent process was an effective virus inactivation process for plasma derivatives, including IGIV [5][6][7][8]. Subsequently, virus inactivation by solvent/detergent was incorporated into other products [9][10][11]. S/D treatment in this study was performed at worst case conditions, i.e.…”
Section: Virus Inactivation and Removalmentioning
confidence: 99%
“…Using lipid solvents and detergents was proved to inactivate SARS-CoV through permeant damage of the lipid components of the viral envelope [39]. This study showed J o u r n a l P r e -p r o o f a drastic drop in the viral titer after one-minute treatment [39]. This raises the mandate of hand as well as personal hygiene as one of the gold standard control measures for not only coronaviruses but also form most enveloped viruses.…”
Section: Some Control Strategies Based On the Physicochemical And Biomentioning
confidence: 87%
“…Coronaviruses are enveloped viruses like influenza, HIV, rabies etc, their envelope composed of a lipid bilayer, which the virus acquires from the host cell membrane while releasing from the infected cells [38]. Using lipid solvents and detergents was proved to inactivate SARS-CoV through permeant damage of the lipid components of the viral envelope [39]. This study showed J o u r n a l P r e -p r o o f a drastic drop in the viral titer after one-minute treatment [39].…”
Section: Some Control Strategies Based On the Physicochemical And Biomentioning
confidence: 99%